The Role of Meditation in Managing Students' Emotions - Hery Gunawan; Ponijan Ponijan; Julia Surya (CV. Rayyan Dwi Bharata, 2024)
This research discusses the role of meditation in managing students' emotions and the importance of implementing meditation in schools so that students can effectively handle their emotions. Meditation is a practice that involves bringing awareness and attention to calm the mind. Meditation has been proven to have a positive impact on students' emotional well-being. The research method applied in this study is a systematic literature review (SLR) to gather and analyze relevant articles. The results of this research indicate that meditation plays a crucial role in managing students' emotions. Students who can effectively manage their emotions are able to self-regulate, exhibit awareness, perform well in school activities, and engage in social interactions effectively.